2019
DOI: 10.3390/su11247211
|View full text |Cite
|
Sign up to set email alerts
|

User, Public, and Professional Perceptions of the Greenways in the Pearl River Delta, China

Abstract: The perception of greenways has been intensively investigated to understand the attitudes of stakeholders and to study the preferences of greenway users. In the Pearl River Delta, there has been a long-term debate on the form and function of greenways in campaign-style development, but few studies have focused on the public perception of greenways. Through both onsite and online investigations, this study obtained first-hand data about the user perceptions of greenways in selected case studies and developed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
3
0
1
Order By: Relevance
“…The next section assessed treetop trails quality using a revised perceived quality of treetop trail scale comprising four dimensions perception of trail facilities (PTF), perception of elevated feeling (PEF), perceptions of trail landscape (PTL), perception of trail design (PTD), and twenty-three related indicators [ 61 ]. This scale was developed based on previous studies on greenways [ 62 , 63 ] and was modified by the present study according to the characteristics of treetop trails. The Cronbach’s α values (range from 0.88 to 0.98) in the present study indicated that the measurement was reliable.…”
Section: Methodsmentioning
confidence: 99%
“…The next section assessed treetop trails quality using a revised perceived quality of treetop trail scale comprising four dimensions perception of trail facilities (PTF), perception of elevated feeling (PEF), perceptions of trail landscape (PTL), perception of trail design (PTD), and twenty-three related indicators [ 61 ]. This scale was developed based on previous studies on greenways [ 62 , 63 ] and was modified by the present study according to the characteristics of treetop trails. The Cronbach’s α values (range from 0.88 to 0.98) in the present study indicated that the measurement was reliable.…”
Section: Methodsmentioning
confidence: 99%
“…As a result of expedient urbanization, it has joined between all-encompassing landscape planning and urban development, a complete discipline for sustainable development, that conserves heritage, and is concerned with social and economic issues [35], [36]. It has become a global movement, for enhancing urban environments [42,43]. It is affected by geographic, economic, cultural, and social aspects [44].…”
Section: Greenways As a Planning Strategymentioning
confidence: 99%
“…Many studies have used questionnaires, field observations, interviews, statistical analysis, and post-use evaluation (POE) to obtain feedback and suggestions from the perspective of users after a greenway has been put into use [32][33][34]. In addition to the accessibility of greenway trails [35], Roe et al found that people have different perceptions of urban green spaces that affect health because of the differences in their own health status, race, gender, and age [36].…”
Section: Literature Reviewmentioning
confidence: 99%